Effects of gastrocnemius functional massage on lower extemity spasticity, spatio- temporal gait variables and fall risk in patients with stroke: A randomized controlled trial - Aziz Dengiz; Serbay Sekeroz; Emre Baskan; Güzin Kara (PLoS ONE, 2025)
Aim This randomized controlled clinical trial investigated the effects of gastrocnemius functional massage (GFM) combined with neurodevelopmental treatment (NDT) on spasticity, gait parameters, and functional mobility in stroke patients. Methods A total of 28 chronic stroke survivors were randomized into an experimental group (EG, n = 13) and a control group (CG, n = 15). Both groups received NDT twice a week for six weeks, while the EG received additional GFM. Spasticity (Modified Ashworth Scale), gait parameters (LegSys), and functional mobility (Timed Up and Go test) were assessed pre- and post-treatment. Results The results showed significant improvements in spasticity within the EG for the hip adductor (p = 0.002), knee extensor (p = 0.006), and ankle plantar flexor muscles (p = 0.002), compared to minimal changes in the CG (p > 0.05). Gait analysis revealed significant improvements in the EG for stride number (p = 0.0001), stride length (p = 0.006), stride time (p = 0.001), and stride velocity (p = 0.002), whereas the CG showed no significant changes (p > 0.05). Functional mobility improvements in the EG included reduced sit-to-stand time (p = 0.021) and total Timed Up and Go time (p = 0.001), indicating enhanced dynamic balance and lower extremity strength. Conclusion These findings suggest that combining GFM with NDT significantly enhances spasticity reduction, gait parameters, and functional mobility in stroke patients. Future studies are needed to explore the long-term effects and underlying mechanisms of this combined approach. Clinical trial registration This study was registered at www.clinicaltrials.gov under the identification number NCT06265753.